1982
DOI: 10.1111/j.1365-2133.1982.tb11680.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin thickness measurement by pulsed ultrasound; its reproducibility, validation and variability

Abstract: The reproducibility of the pulsed ultrasound technique for the determination of skin thickness was investigated, using two independent observers. No systematic difference was found and a high correlation was obtained. Studies were also undertaken to validate the pulsed ultrasound technique as a measure of true skin thickness. Skin thickness determined in vitro was found to be greater than when in vivo determinations were made by either the pulsed ultrasound or a xeroradiographic technique, probably due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
116
2
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 6 publications
15
116
2
2
Order By: Relevance
“…Atualmente, há grande número de apresentações comerciais disponíveis; entretanto, há poucos estudos científicos de longo prazo que comprovem a real durabilidade de cada produto, ou que forneçam comparações entre os mesmos [8][9][10] . A ultrassonografia, utilizada previamente em vários estudos para mensuração da espessura cutânea em indiví-duos sãos e com sequelas de queimadura, demonstrou ser um método vantajoso, por ser aplicável em qualquer parte do corpo, não utilizar radiação, ter baixo custo, alta reprodutibilidade e baixa variabilidade entre observadores [10][11][12][13][14] . Em nossa instituição, a ultrassonografia de partes moles foi realizada com o aparelho ATL Philips HD 5000 (Milwalkee -USA), com sonda de pequenas partes de 14 MHz.…”
Section: Introductionunclassified
“…Atualmente, há grande número de apresentações comerciais disponíveis; entretanto, há poucos estudos científicos de longo prazo que comprovem a real durabilidade de cada produto, ou que forneçam comparações entre os mesmos [8][9][10] . A ultrassonografia, utilizada previamente em vários estudos para mensuração da espessura cutânea em indiví-duos sãos e com sequelas de queimadura, demonstrou ser um método vantajoso, por ser aplicável em qualquer parte do corpo, não utilizar radiação, ter baixo custo, alta reprodutibilidade e baixa variabilidade entre observadores [10][11][12][13][14] . Em nossa instituição, a ultrassonografia de partes moles foi realizada com o aparelho ATL Philips HD 5000 (Milwalkee -USA), com sonda de pequenas partes de 14 MHz.…”
Section: Introductionunclassified
“…For exam- ple, dermal thickness in the medial forearm varies from 0.6 to 1.0 mm in women and from 0.8 mm to 1.2 mm in men. In the lateral arms or legs, Tan et al 26 found a mean dermal thickness of 1.32 mm, on the chest of 1.62 mm, and on the back of 2.50 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Традиционно инсулин вводится в подкожно-жировую клетчатку. Интрадермальные инъекции по скорости попадания инсулина в кровоток сопоставимы с внут-ривенными инфузиями, но точное попадание в дерму техниче-ски очень сложно, так как ее толщина составляет не более 3 мм [13][14][15]. При внутримышечном введении инсулина короткого действия достигается быстрый эффект, сравнимый с введением аналогов ультракороткого действия, однако отмечается значи-тельная вариабельность всасывания [16].…”
Section: /2010unclassified